PENGARUH LOCUS OF CONTROL TERHADAP PERILAKU DISFUNGSIONAL AUDITOR - MANATAP BERLIANA LUMBAN GAOL (JURNAL ILMIAH KOHESI, 2021)
Dysfunctional behavior of auditors is associated with a decrease in audit quality (General Board Supervision 2000). Whileprevious studies have shown that dysfunctional behavior of auditors is a widespread problem (Smith 1995; Otley and Pierce1995). This study adequately explains the causal or determining factors of deviant forms of behavior. This study developedand tested a theoretical model that identifies locus control, as an antecedent of attitudes towards dysfunctional behavior ofauditors. Using path analysis techniques, the survey results from 113 auditors support theoretical models.